A framework for luck egalitarianism in health and healthcare. Issue 2 (6th February 2014) - Albertsen, Andreas; Knight, Carl
Abstract : Several attempts have been made to apply the choice-sensitive theory of distributive justice, luck egalitarianism, in the context of health and healthcare. This article presents a framework for this discussion by highlighting different normative decisions to be made in such an application, some of the objections to which luck egalitarians must provide answers and some of the practical implications associated with applying such an approach in the real world. It is argued that luck egalitarians should address distributions of health rather than healthcare, endorse an integrationist theory that combines health concerns with general distributive concerns and be pluralist in their approach. It further suggests that choice-sensitive policies need not be the result of applying luck egalitarianism in this context.